Narratives and Mediated Speech: La Malinche in Amor y conquista (1999) by Marisol Martín del Campo (Anclajes, 2026)
The novel Amor y conquista (1999), by Marisol Martín del Campo, rewrites the figure of La Malinche from an Indigenous and gender-based perspective. Through a polyphonic narration and stylized language echoing native speech patterns, the novel gives voice to the conquered and critically reconstructs the figure of Malinalli. Rather than a traitor, she emerges as a self-aware woman, cultural mediator, and symbol of mestizaje. The article examines this reconfiguration in dialogue with the discourses that have historically shaped the image of La Malinche, showing how contemporary fiction challenges the regimes of representation of Indigenous women in the national imaginary.
Keywords: Marisol Martín del Campo; La Malinche; Postcolonial Literature; Literary Criticism; 20th Century